Fracture Failure Characteristics of Jointed Sandstone under Uniaxial Compression - Ronghua Su; Xiaolin Liu (Geofluids)
Jointed rocks are ubiquitous in the complex environments (coupled heat and moisture conditions) encountered in deep underground mining. To investigate the influence of the joint locations on the strength, deformation, and fracture failure characteristics of the jointed sandstone, uniaxial compression tests were carried out for sandstone specimens in a natural moisture state and with a preexisting joint in different locations. The entire test process was recorded by a dynamic strain acquisition system and digital speckle observation equipment. The results show that the peak strength weakening of the jointed sandstone was different with different joint positions. The residual strength and lateral deformation of the jointed sandstone were affected by the location of the joint. The joint locations dominated the evolution of the fractures in the sandstone and influenced the failure mode. The fracture evolution in sandstone with a joint in the middle was characterized by the closure of the fractures away from the starting position and was finally destroyed by the combination of shearing and splitting. The evolution of fractures in the sandstone with a joint at the bottom was stopped on the other side, which was eventually sheared across the joint. Besides, based on fractal theory, the fracture distribution on the specimen surface was analysed at certain points (first appearance of fracture, peak point) and the final destruction state during the fracture evolution. The fractal dimension was obtained, which further characterizes the fracture evolution and failure of sandstone with a joint at different locations.